The Impact of Implementation of the Regulation of Minister of Marine and Fisheries Number 56 and 57 of 2014 to the Fishing Industry in Bitung, North Sulawesi, and Indonesia - Stanny S Rawung; Ficke H Rawung (International Journal of Applied Business and International Management, 2018)
The fishing industry is the dominant driver of the Economy in Bitung. The major contribution of fishing industry to Bitung City made this city known by the term "Skipjack". With the enactment of the Regulation of the Minister of Marine and Fisheries No 56 of 2014 on Temporary Cessation (Moratorium) Licensing of Fish in Regional Fisheries Management of the Republic of Indonesia and the Regulation of the Minister of Marine and Fisheries No. 57 of 2014 regarding the Second Amendment to the Regulation of the Minister of Marine and Fisheries No. 30 / MEN / 2012 on Business fisheries Regional fisheries Management in the Republic of Indonesia., brought a huge impacts for the fisheries industry in Bitung. The implementation of the new fishing regulation did not only affect the fishing industry in Bitung, but also throughout the economy on the city of Bitung and North Sulawesi. This research analyzed the impact of the application of the regulation. In this study, the researchers examined the Fishing Industry Bitung city before and after implementation of the fishing regulation. The study also included the analysis of the fish/raw material supply chain which most severely affected by the new fishing regulation and also discuss the multiplier effects from the application of the fishing regulation.